A novel endpoint for the assessment of chemotherapy‐induced peripheral neuropathy in rodents: biomechanical properties of peripheral nerve. Issue 2 (16th August 2017) - Liu, Chang‐Ning; Berryman, Edwin; Zakur, David; Shoieb, Ahmed M.; Pardo, Ingrid D.; Boucher, Magalie; Somps, Chris J.; Bagi, Chedo M.; Cook, Jon C.
Abstract: Chemotherapy‐induced peripheral neuropathy (CiPN) is a frequent adverse effect in patients and a leading safety consideration in oncology drug development. Although behavioral assessment and microscopic examination of the nerves and dorsal root ganglia can be incorporated into toxicity studies to assess CiPN risk, more sensitive and less labor‐intensive endpoints are often lacking. In this study, rats and mice administered vincristine (75 μg kg −1 day −1, i.p., for 10 days in rats and 100 μg kg −1 day −1, i.p., for 11 days in mice, respectively) were employed as the CiPN models. Behavioral changes were assessed during the dosing phase. At necropsy, the sural or sciatic nerve was harvested from the rats and mice, respectively, and assessed for mechanical and histopathological endpoints. It was found that the maximal load and the load/extension ratio were significantly decreased in the nerves collected from the animals dosed with vincristine compared with the vehicle‐treated animals ( P < 0.05). Additionally, the gait analysis revealed that the paw print areas were significantly increased in mice ( P < 0.01), but not in rats following vincristine administration. Light microscopic histopathology of the nerves and dorsal root ganglia were unaffected by vincristine administration. We concluded that ex vivo mechanical properties of the nerves is a sensitive endpoint, providing a new method to predict CiPN in rodent. Gait analysis may also be a useful tool in these pre‐clinical animal models. Abstract : Rats and mice administered vincristine were employed as the chemotherapy‐induced peripheral neuropathy models. Behavior and ex vivo sural (rats) or sciatic nerve (mice) were assessed. It was found that the load and the load/extension ratio were decreased in the nerves collected from the animals dosed with vincristine. We concluded that mechanical properties of the nerves are a sensitive endpoint for chemotherapy‐induced peripheral neuropathy prediction.